Strategies to Strengthen Brand Resilience in the Digital Age: Synergy between Innovation and Customer Experience in the Post-Pandemic Market - Askarno Askarno (Journal of Strategic Marketing and Applied Economics, 2025)
In the dynamic digital era and post-pandemic conditions, companies face new challenges in maintaining brand resilience amid rapid changes in consumer preferences and increased competition. Brand resilience depends not only on product innovation, but also on a consistent and valuable customer experience. This research aims to explore the synergy between innovation and customer experience in building sustainable brand resilience. Using qualitative methods, the study collected data through in-depth interviews with marketing managers and customers from various companies in the retail and digital services sectors. Thematic analysis reveals that relevant innovations and interactive customer experiences are able to reinforce positive perceptions and loyalty of brands, even in conditions of market uncertainty. These findings highlight the importance of an approach that combines strategic innovation with a responsive customer experience, which not only improves competitiveness but also adds long-term value to brands. The implications of this study provide practical guidance for companies to design brand resilience strategies that are relevant to customer needs and the development of digital technology.